Optimization and verification of changes made to US-EPA 1623 Method to analyse for the presence of Cryptosporidium and Giardia in water - Khoza, M. N. L. (Mtetwa) (Vaal University of Technology, 2011)
Methods for detecting the presence of Cryptosporidium oocysts and Giardia cysts have been developed and continuous improvement is being done to improve the recovery rate of the target protozoa. Rand Water has adopted their method for isolation and detection of Cryptosporidium oocysts and Giardia cysts in water from United State Environmental Protection Agency (US-EPA) Method 1623, 1999. In 2005 changes were made by US-EPA to the Method 1623. A study was done to improve the performance of the Rand Water Method 06 (2007) used for isolation and detection of Cryptosporidium oocysts and Giardia cysts. Three methods namely: Rand Water Method 06 (2007), US-EPA Method 1623 (2005) and Drinking Water Inspectorate standard operating procedures (2003) were compared and key different steps in the methods were identified (wrist action speed, centrifuge speed, immunomagnetic separation procedures and addition of pre-treatment steps). Different experiments were conducted to verify and evaluate the difference between two wrist action shaker speeds, three different centrifuge speeds, two slightly different immunomagnetic separation procedures and when a pre-treatment step was included in the method. Three different types of water matrices (reagent grade water, drinking water and raw water) were used for the experiments and secondary validation. Data obtained from the experiments and secondary validation was statistically analyzed to determine whether there was a significant difference in the recovery of Cryptosporidium oocysts and Giardia cysts. Secondary validation of the Rand Water Method 06 (2007) was performed by implementing the study experiments‟ findings into the method. The results indicated an increase in the recovery rate of Cryptosporidium oocysts and Giardia cysts when data was compared with the previous secondary validation report. The mean recovery of Cryptosporidium oocysts in reagent grade water samples increased from 31% to 55%, drinking water samples increased from 28% to 44% and raw water decreased from 42% to 29%. The mean recovery of Giardia cysts in reagent grade water samples increased from 31% to 41%, drinking water samples increased from 28% to 46% and raw water decreased from 42% to 32%. Furthermore, even though the recovery rate of raw water decreased the use of pre-treatment buffer reduced the number of IMS performed per sample by reducing the pellet size. Enumeration of microscope slides was also easier as there was less background interference. The optimization of the Rand Water Method 06 (2007) was successful as the recovery rate of Cryptosporidium oocysts and Giardia cysts from water increased. All the changes that were verified and that increased the recovery rate were incorporated into the improved Rand Water Method 06.
M. Tech. (Department of Biosciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: US-EPA 1623; Cryptosporidium oocysts; Giardia cysts; Water analysis; Protozoa in water; Rand Water Method 06 (2007); Drinking water Inspectorate standard operating procedures (2003); Reagent grade water; Raw water; Drinking water; 572.539; Water quality.; Biochemistry.; Drinking water.; Water, Microbiology.